ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI DI KAMPUNG BUYUNG-BUYUNG KABUPATEN BERAU: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI DI KAMPUNG BUYUNG-BUYUNG KABUPATEN BERAU - Andi Rizky Pradana (ECO-BUILD, 2025)
The study aims to determine the partial and simultaneous influence of land area, capital, labor, technology, and production costs on the increase in rice farmer income in Kampung Buyung-Buyung, Tabalar District, Berau Regency. Based on the analysis of the data and discussion presented, it is concluded that the variables of land area, selling price, and rice production significantly and positively affect the level of rice farmer income in Kampung Buyung-buyung, Tabalar District, Berau Regency. Meanwhile, the variable of production costs significantly and negatively affects the level of rice farmer income in Kampung Buyung-buyung, Tabalar District, Berau Regency.Based on the analysis and discussion, the variables of land area (X1), selling price (X2), production yield (X3), and production costs (X4) simultaneously have a significant and positive influence on the level of rice farmer income in Kampung Buyung-buyung, Tabalar District, Berau Regency.